2001
DOI: 10.1161/01.str.32.7.1621
|View full text |Cite
|
Sign up to set email alerts
|

Constraint-Induced Therapy of Chronic Aphasia After Stroke

Abstract: Abstract-Patients with chronic aphasia were assigned randomly to a group to receive either conventional aphasia therapy or constraint-induced (CI) aphasia therapy, a new therapeutic technique requiring intense practice over a relatively short period of consecutive days. CI aphasia therapy is realized in a communicative therapeutic environment constraining patients to practice systematically speech acts with which they have difficulty. Patients in both groups received the same amount of treatment (30 to 35 hour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
515
0
39

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 585 publications
(591 citation statements)
references
References 20 publications
22
515
0
39
Order By: Relevance
“…However, no further improvement during a 6-month follow-up period during which patients received approximately 2 hr0week outpatient language therapy. Similarly, Pulvermueller et al (2001) demonstrated more improvement of language functions after 2 weeks of intensive treatment (3 hr0day) than after the same number of treatment hours extended across several weeks.…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations
“…However, no further improvement during a 6-month follow-up period during which patients received approximately 2 hr0week outpatient language therapy. Similarly, Pulvermueller et al (2001) demonstrated more improvement of language functions after 2 weeks of intensive treatment (3 hr0day) than after the same number of treatment hours extended across several weeks.…”
Section: Introductionmentioning
confidence: 88%
“…All patients received the same standardized intensive training, Constraint-Induced Aphasia Therapy (CIAT, Meinzer et al, 2005;Pulvermueller et al, 2001). CIAT is an adaption of Constraint-Induced Movement Therapy (CIMT), a well-evaluated therapeutic tool for the treatment of poststroke paresis (Taub et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Owing to its incidental (associative) learning principle, the model is suitable for high-frequency training programs in brain-damaged populations. Recent experimental (Basso and Caporali, 2001;Pulvermuller et al, 2001) and review work (Bhogal et al, 2003a;Bhogal et al, 2003b;Robey, 1994) on aphasia therapy has suggested that training intensity may in fact play the most important role in predicting treatment success in aphasia. Furthermore, in a still-ongoing study, we collected the first evidence that some patients with aphasia may benefit from our word-learning model.…”
Section: D-amphetamine Boosts Language Learning C Breitenstein Et Almentioning
confidence: 99%